BIOSYNTHESIS OF SILVER NANOPARTICLES USING TRACHYSPERMUM AMMI AND EVALUATION OF THEIR ANTIBACTERIAL ACTIVITIES - NEELU CHOUHAN; RAJESH KUMAR MEENA (International Journal of Pharma and Bio Sciences, 2015)
Bio-chemical reduction method was employed to synthesise the silver nanoparticles (Ag NPs) by aging the mixture of the aqueous extract of the Trachyspermum Ammi (TA, Ajwain) seeds and AgNO3 solution at different time interval. Reaction time of AgNO3 and TA could accelerate the reduction rate of Ag+ and affect AgNPs size and concentration of NPs. X-ray diffraction (XRD) studies confirms the formation of pure AgNPs that crystallized into the cubic shape particles of size 36nm. Surface plasmon resonance band centred at 420-430 nm was recognised as the first exitonic peak of UV-Vis absorption spectra that confirmed the presence of the AgNPs. FTIR results TA supported AgNPs showed decrease in intensity of peaks at 3497 and 1695 cm-1 with respect to the pure TA indicating the involvement of NH2, O-H, carbonyl group and C=C stretching in formation of TA-AgNPs aggregates. The C-O-C and C-N stretching suggested the presence of the bonding between the phytochemicals and AgNPs. TA extract play a role of capping and reducing agent for converting silver ions into silver nanoparticles. Pronounce effect of the aging on AgNPs concentration and particle size, was exhibited by the system. As synthesized AgNPs was characterized using transmission electron microscopy (TEM), UV- Vis spectrophotometer (UV-Vis), Fourier transformation infrared (FTIR) spectroscopy and XRD. Study demonstrated the inside view of the most probable mechanism of the biosynthesis of AgNPs and the potent antagonistic activity against bacteria, which possess potential applications in medicine and pharmaceutical fields.